Ecoviolence studies human exploitation and environmental crime - Stoett, Peter 1965-; Omrow, Delon Alain (Cambridge University Press, 2025)
Ecoviolence, defined broadly as the intersection between human-human exploitation and the destruction of nature, is one of the defining features of our time. This book collects ten case studies examining the intersection between the exploitation of human beings and environmental harm. Topics discussed include the wildlife trade, ecoviolence at sea, natural resource exploitation in Latin America and Africa, human trafficking induced by extreme weather events, climate change-related language death, and the confluence of drug cartels and environmental destruction. The book argues that Ecoviolence Studies has emerged as an expanded, multidisciplinary field in its own right, and that policy responses and the search for environmental and social justice should reflect accumulated knowledge in this area. It is an insightful volume for researchers and graduate students working in green criminology, Earth system governance, environmental politics, human rights, environmental and international law, and related areas